Pelatihan Sintesis Edible Film Plastik Sebagai Alternatif Ramah Lingkungan Dalam Pengemasan Pempek - Diana Novitasari; Alifia Okta Billa Margita; Destiana Destiana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Synthetic plastic used as a food product wrapper, including Pempek, has become a serious source of environmental problems. To reduce the negative impact of the waste, community service activities were carried out in the form of training in making plastic film edible as an alternative to pempek wrapping. This training focuses on pempek business actors, with the aim of providing understanding and skills in producing and using plastic film edible. The training material includes the selection of environmentally friendly raw materials, biodegradable plastic production techniques, and application as pempek wrapper. The evaluation is carried out through the measurement of participants' understanding, the quality of the plastic produced, and the market reception of pempek that uses biodegradable wrapping. The training results showed an increase in the understanding of participants related to environmental sustainability and their ability to produce biodegradable plastic. Market acceptance of pempek with environmentally friendly wrapping also provides a positive encouragement to the application of sustainable practices in the culinary sector. Thus, this community service activity is expected to be a concrete step in reducing the use of conventional plastic in the food industry, especially in pempek products. In addition, this training is expected to have a positive impact on community environmental awareness and encourage sustainable practices in the use of food products wrapping